AN ASSESSMENT OF THE ROLE OF ABO BLOOD GROUP ON MALARIA INFECTION IN A HETEROGENOUS COMMUNITY, KADUNA – NIGERIA: ABO blood group and malaria - Salman, Abdulmalik Abdullahi; Ibrahim, Halima Sadiya; Abdullahi, Aliyu Dantani; Usman, Aliyu Mohammed; Shuaibu, Mohammed Nasir (FUDMA JOURNAL OF SCIENCES, 2025)
Malaria is a global public health concern considered a leading cause of morbidity. A cross-sectional study was carried out to assess the role of ABO blood group on malaria between April and June 2024. A total of 120 blood samples were collected from patients aged five and above, except pregnant women undergoing malaria test at Primal Diagnostic Service in Kaduna state. Blood samples were collected from patients and stained with Field stain using standard parasitological techniques. Agglutination techniques using monoclonal anti-sera A, B and D were used to determine the ABO blood groups and a full blood count analysis was carried out to check some hematological parameters. Data generated was analysed using ANOVA test and statistical significance level was set at P
Keywords: Malaria; ABO Blood group; Parasitaemia; Parameters